Aceh’s new cultural leader : former separatist now guardian of state - Mushahid Ali (2014)
Former Aceh separatist leader Malik Mahmud has become Wali Nanggroe (guardian of state). How will he reconcile Aceh’s push for its own identity with being part of the Indonesian republic?